ANALISIS PENDAPATAN ASLI DAERAH DAN TINGKAT KEMANDIRIAN KOTA SAMARINDA - -, HERSI KRISTIANENSI (EKONOMIA, 2017)
The formulation of the problem whether the realization of local revenue (PAD) in accordance with the planned in 2013 and 2014 and whether the level of financial independence samarinda region increased.The basic theories used are public sector accounting and regional finance. This report calculates from the report of the target and realization of local revenue and revenue of indigenous city of samarinda in 2013 and 2014. The analysis tool used is the ratio of effectiveness and independence ratio.The results of the 2013 study show that the realization of local revenue target (PAD) in accordance with the plan even exceeded the target for 2014 the ability of the government in realizing revenue revenues (PAD) compared with the targeted is not in accordance with the plan. These results indicate a decrease in effectiveness level in 2014. The results of 2013 regional financial self-sufficiency in 2013 and 2014 can be seen that the level of financial ability has increased.Thus from the results of the study it can be concluded that for the formulation of the first problem is not in accordance with the hypothesis proposed and